(untitled) (Albayan Scientific Journal, 2023)
The noxious incidence of undesirable plants, also known as weeds, is one of the major constraints to world agricultural production. Weeds are plants that under certain conditions cause economic and social harm to the farmers. Weeds have always been considered strong competitors of crop plants; and today, they form an inseparable part of agronomic systems and inflict losses on crop plants. To evaluate various herbicides for controlling weeds wild oat- in wheat fields, an experiment was conducted field to appraise the efficacy of herbicides against weed growth and their influence on growth and yield. Treatment consisted of Galant Super (Haloxyfop-R-methyl 10.8% EC), three concentrations of pesticides were used respectively (25%,50%,75%). Spraying was carried out using a back sprayer. Results showed that herbicide reduced weed population considerably .The most effective was with a concentration 75% reduced weed by 98.7%, and none of concentrations the herbicides hurt the crop.